2000
DOI: 10.1111/j.1744-7348.2000.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of three berry fruit species using nodal segments from field‐grown plants

Abstract: Plant micropropagation of blueberry (Vaccinium corymbosum L. cv. Berkeley), blackberry (Rubus sp. cv. Smoothstem) and raspberry (Rubus idaeus L. cv. Gradina) was carried out from nodal segments of adult field-grown plants. Hardwood and softwood cuttings were studied as explant sources. The cultures successfully established were softwood from all three species, and hardwood only from blueberry. Shoot-bud establishment from blueberry was achieved by culturing explants in WPM salts with MS vitamins for 15 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
15

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 12 publications
(11 reference statements)
2
34
0
15
Order By: Relevance
“…A este respecto, se han probado técnicas como la organogénesis directa e indirecta utilizando hojas de diferentes variedades comerciales (Isac, 2009) y la criopreservación de brotes apicales (Wang et al, 2005;Gupta y Reed, 2006). Algunos sistemas para la micropropagación de frambuesa han utilizadoel medio de cultivo MS (Muashige y Skoog, 1692) semisólido y líquido en inmersión temporal complementado con bencil amino purina (BAP), ácido giberélico (AG 3 ) y ácido ascórbico (Jones y Flores, 2007); también se reporta el uso de N 6 -benciladenina, tidiazuron y zeatina (Reed, 1991;Popescue Isac, 1999;González et al, 2000;Vujović et al, 2009). …”
Section: Introductionunclassified
See 1 more Smart Citation
“…A este respecto, se han probado técnicas como la organogénesis directa e indirecta utilizando hojas de diferentes variedades comerciales (Isac, 2009) y la criopreservación de brotes apicales (Wang et al, 2005;Gupta y Reed, 2006). Algunos sistemas para la micropropagación de frambuesa han utilizadoel medio de cultivo MS (Muashige y Skoog, 1692) semisólido y líquido en inmersión temporal complementado con bencil amino purina (BAP), ácido giberélico (AG 3 ) y ácido ascórbico (Jones y Flores, 2007); también se reporta el uso de N 6 -benciladenina, tidiazuron y zeatina (Reed, 1991;Popescue Isac, 1999;González et al, 2000;Vujović et al, 2009). …”
Section: Introductionunclassified
“…In this regard, techniques like direct and indirect organogenesis have been used, using leaves from different commercial varieties (Isac, 2009) and cryopreservation of apical shoots (Wang et al, 2005;Gupta and Reed, 2006). Some systems for raspberry micro propagation have used MS medium (Muashige and Skoog, 1692) semisolid and liquid in temporary immersion supplemented with benzyl amino purine (BAP), gibberellic acid (GA 3 ) and ascorbic acid (Jones and Flores, 2007); the use of N 6 -benzyladenine, thidiazuron and zeatin (Reed, 1991;Popescue Isac, 1999;González et al, 2000;Vujović et al, 2009) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro derived shoots (> 1.5 cm long) were rooted ex vitro in shredded sphagnum moss in pots (Qu et al 2000). Although an auxinpretreatment was found unnecessary for ex vitro rooting of blueberries (Gonzalez et al 2000), Debnath (2004a) found 85 to 95% rooting in lowbush blueberry when microshoots were dipped in 4.9 mM indole-3-butyric acid (IBA) before planting in 2 peat:1 perlite (vol/vol) medium. For ex vitro rooting, the microcuttings are generally maintained in a mist chamber with very high relative humidity (RH 95%) and then transferred to a greenhouse (85% RH) for acclimatization.…”
Section: Rooting and Acclimatization Of Micropropagated Shootsmentioning
confidence: 99%
“…The first in vitro callus formation was induced by Nickerson and Hall (1976) in lowbush blueberry, followed by Lyrene (1978) in rabbiteye (V. Ashei Reade) and Nickerson (1978a, b) in lowbush blueberry. Subsequently, tissue culture techniques for axillary shoot proliferation have been developed for lowbush blueberry (Frett and Smagula 1983;Debnath 2004a), highbush blueberry (V. corymbosum L.) (Zimmerman and Broome 1980;Gonzalez et al 2000), rabbiteye blueberry (Lyrene 1980) and cranberry (V. macrocarpon Ait.) (Marcotrigiano and McGlew 1991;Debnath and McRae 2001a;Debnath and McRae 2005), lingonberry (V. vitis-idaea L.) (Hosier et al 1985;Reed and Abdelnour-Esquivel 1991;Debnath and McRae 2001b;Jaakola et al 2001;Debnath 2005a, b) and bilberry (V. myrtillus L.) (Jaakola et al 2001) .…”
Section: Propagation Via Axillary Shoot Proliferationmentioning
confidence: 99%
See 1 more Smart Citation